2006
DOI: 10.4037/ajcc2006.15.6.595
|View full text |Cite
|
Sign up to set email alerts
|

Use of Local Anesthesia for Arterial Punctures

Abstract: • Background Except for intravenous therapy, arterial access is the most common invasive procedure performed on critically ill patients. Arterial puncture is a source of pain and discomfort. Intradermal injection of lidocaine around the puncture site decreases the incidence and severity of localized pain when used before arterial puncture. • Objective To review the recommendations and studies related to the use of intradermal lidocaine to decrease pain during arterial punctures. •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…Hudson et al18 reviewed studies and recommendations related to the use of intradermal lidocaine to reduce pain during arterial punctures. The findings showed that the use of intradermal lidocaine before arterial puncture clearly decreased pain associated with the procedure and did not interfere with the success rate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hudson et al18 reviewed studies and recommendations related to the use of intradermal lidocaine to reduce pain during arterial punctures. The findings showed that the use of intradermal lidocaine before arterial puncture clearly decreased pain associated with the procedure and did not interfere with the success rate.…”
Section: Resultsmentioning
confidence: 99%
“…The use of local anesthesia facilitates successful IV cannulation and ABG sampling because of the reduction of associated pain and anxiety, which helps patients remain still during the procedure. According to Hudson et al,18 the administration of local anesthesia for ABG sampling was helpful in increasing the success rates of gaining arterial access because it minimizes patient movement during the procedure. Similarly, Crowley et al8 evaluated the success rate of injection and topical anesthetics; all reviewed studies indicated that the success rates were enhanced by the administration of local anesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations